Powtoon Animation Effects on ICT Learning Interest: A Madrasah Experiment in Indonesia - Hadi Gunawan Sakti; Abdurrahman (Lembaga Bale Literasi, 2026)
The integration of interactive multimedia in education has gained considerable attention, yet its practical application in Indonesian vocational settings remains limited. This study examines the effectiveness of Powtoon-based interactive learning media on students' learning interest in ICT subjects at MA Darusshiddiqien NW Mertak Paok, Central Lombok. Employing a quantitative approach with a one-group pretest-posttest design, data were collected from 26 students of class XI-IPS using a 22-item Likert-scale questionnaire. The chi-square test yielded a calculated value of 19.774, which exceeded the table value of 9.488 at a 5% significance level with df = 4. These results indicate a statistically significant effect, leading to the rejection of the null hypothesis. The findings suggest that Powtoon-based interactive media contributes positively to enhancing students' learning interest in ICT education. However, the small sample size and single-group design limit the generalizability of the results. Future research should consider larger samples and comparative designs to validate these findings across diverse educational contexts